2022
DOI: 10.1101/2022.05.25.493445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

De novo mapping of the apicomplexan Ca2+-responsive proteome

Abstract: Apicomplexan parasites cause persistent mortality and morbidity worldwide through diseases including malaria, toxoplasmosis, and cryptosporidiosis. Ca2+ signaling pathways have been repurposed in these eukaryotic pathogens to regulate parasite-specific cellular processes governing the transition between the replicative and lytic phases of the infectious cycle. Despite the presence of conserved Ca2+-responsive proteins, little is known about how specific signaling elements interact to impact pathogenesis. We ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 152 publications
0
10
0
Order By: Relevance
“…Gene ontology enrichment analysis was performed as described (Herneisen et al, 2022 ). Sets of gene ontology terms from the differentially regulated (SPARK-dependent) and background proteome (all proteins with quantification values in the SPARK-AID mass spectrometry experiment) were downloaded from ToxoDB.org (Molecular Function, Computed evidence, P-Value cutoff set to 1).…”
Section: Enrichment Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Gene ontology enrichment analysis was performed as described (Herneisen et al, 2022 ). Sets of gene ontology terms from the differentially regulated (SPARK-dependent) and background proteome (all proteins with quantification values in the SPARK-AID mass spectrometry experiment) were downloaded from ToxoDB.org (Molecular Function, Computed evidence, P-Value cutoff set to 1).…”
Section: Enrichment Analysismentioning
confidence: 99%
“…Samples were reduced, alkylated, and digested as described previously (Herneisen et al, 2022 ). In brief, the eluates were reduced with 5 mM TCEP for 20 minutes at 50°C.…”
Section: Proteomics Sample Preparation and Tmt Labelingmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed downregulation of phosphosites belonging to proteins involved in ubiquitin transfer, such as an E2 enzyme and a ubiquitin family protein with a C-terminal extension. The precise pathways regulated by TgPKG remain to be defined; however, recent studies triggering PKG activity in T. gondii (Chan et al, 2023 ;Herneisen et al, 2022 ) or related Plasmodium spp. (Alam et al, 2015 ;Balestra et al, 2021 ;Brochet et al, 2014 ) suggested that PKG substrates relevant for egress reside at the parasite periphery and ER, as observed for the overlapping PKG and SPARK targets here.…”
Section: Spark Functionally Interacts With Pka and Pkgmentioning
confidence: 99%
“…Several recent studies have sought to characterize the downstream targets of second messenger kinases in apicomplexans, including PKA, PKG, and calcium-dependent protein kinases (Alam et al, 2015 ;Balestra et al, 2021 ;Brochet et al, 2014 ;Chan et al, 2023 ;Herneisen et al, 2022 ;Jia et al, 2017 ;Nofal et al, 2022 ). The second messenger networks in these parasites are intricately interwoven, with documented crosstalk between parasite cAMP, cGMP, and calcium signaling cascades.…”
Section: Introductionmentioning
confidence: 99%